2007
DOI: 10.4049/jimmunol.178.11.6984
|View full text |Cite
|
Sign up to set email alerts
|

Cytopiloyne, a Polyacetylenic Glucoside, Prevents Type 1 Diabetes in Nonobese Diabetic Mice

Abstract: Some polyacetylenes from the plant Bidens pilosa have been reported to treat diabetes. In this study, we report that the cytopiloyne from B. pilosa, which is structurally different from the above-mentioned polyacetylenes and inhibits CD4+ T cell proliferation, effectively prevents the development of diabetes in nonobese diabetic mice as evidenced by a normal level of blood glucose and insulin and normal pancreatic islet architecture. Cytopiloyne also suppresses the differentiation of type 1 Th cells but promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 60 publications
6
63
0
3
Order By: Relevance
“…Remarkably, 12- to 30-week-old NOD mice treated with cytopiloyne showed normal levels of blood glucose (<200 mg/dL) and insulin (1-2 ng/mL). Consistent with T1D incidence, cytopiloyne delayed and reduced the invasion of CD4 + T cells into the pancreatic islets [20]. Albeit less effective than cytopiloyne ( 19 ), 3- β -D-glucopyranosyl-1-hydroxy-6( E )-tetradecene-8,10,12-triyne ( 17 ), and 2- β -D-glucopyranosyloxy-1-hydroxy-5( E )-tridecene-7,9,11-triyne ( 16 ) also decreased T1D development in NOD mice.…”
Section: Antidiabetic Propertiesmentioning
confidence: 95%
“…Remarkably, 12- to 30-week-old NOD mice treated with cytopiloyne showed normal levels of blood glucose (<200 mg/dL) and insulin (1-2 ng/mL). Consistent with T1D incidence, cytopiloyne delayed and reduced the invasion of CD4 + T cells into the pancreatic islets [20]. Albeit less effective than cytopiloyne ( 19 ), 3- β -D-glucopyranosyl-1-hydroxy-6( E )-tetradecene-8,10,12-triyne ( 17 ), and 2- β -D-glucopyranosyloxy-1-hydroxy-5( E )-tridecene-7,9,11-triyne ( 16 ) also decreased T1D development in NOD mice.…”
Section: Antidiabetic Propertiesmentioning
confidence: 95%
“…Many phytocompounds are believed to be immunomodulatory, we and others have recently demonstrated such activities for a series of anti-inflammatory phytocompounds including shikonin, an inhibitor of TNF-α mRNA maturation [9] or transcription [6], and emodin, which represses the inflammatory response [10,11]. Another unique immuno-modulatory compound, cytopiloyne, recently isolated from the Asteraceae plant, Bidens pilosa [12], has also been reported to decrease the symptoms of autoimmune disease in mouse type I diabetes [13]. We have observed that both emodin and cytopiloyne can effectively modulate human dendritic cell function (unpublished results).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Th1 cells and type 1 cytokines promote T1D in NOD mice whereas Th2 cells ameliorate/suppress the disease under certain experimental conditions. In fact, there is evidence that administration of immunomodulatory drugs protects against progression of T1D by promoting a shift from a Th1 to a Th2 response [5,6] . However, so far, there is no conclusive evidence showing that a Th2 shift in the cytokine pattern leads to disease protection.…”
Section: Disease-modifying Immunotherapy For the Management Of Autoimmentioning
confidence: 99%
“…This suggests that new intervention therapies combining inhibitory antibodies and immunoregulatory agents are warranted. Also, drugs of diverse chemical nature have been employed successfully as prophylactic intervention in animal models of T1D, without apparent toxic effects [5] .…”
Section: Disease-modifying Immunotherapy In Autoimmune Diabetesmentioning
confidence: 99%